Overview of clinical pharmacology in cancer 2 - Kolesar, Jill (Henry Stewart Talks, 2017)
Principles of pharmacodynamics, Mechanisms of action of anticancer agents, Evolution from non-specific DNA damagers to targeted therapies, Integrated pharmacokinetics, dynamics and genomics dose response model